A comparative study of spontaneous versus induced labor in primi and multiparous women at tertiary care centre - Damor, Priyanka; Chavhan, Suresh Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Objectives of the study were to compare progression of spontaneous versus induced labor in primigravida and multigravida women. Methods: Pregnant women admitted in labor room of RNT medical college Udaipur during January 2021 to June 2021 were selected for this study. A total of 200 pregnant women were selected and divided into two groups. Women in group A were induced while in group B were women with spontaneous onset of labour. Labor progression in both was compared. Results: In group A, the mean duration of active phase in primigravida was 4.08+2.30 hr. In group A, the mean duration of the second stage in a primigravida was 25.5+8.15 min and in a multigravida was 17.38+9.95 min. In group B,the mean duration of second stage in a primigravida was 41.3+9.6 min, while in a multigravida was 22.72+6.2h. The mean duration of active phase in group A in the primigravida and multigravida was almost similar, showing that induction does not have any effect on the duration of active phase. The mean duration of the second stage of group A in primigravida was 25 min and multigravida were 17 min showing that induction reduces the duration of the second stage. Conclusions: Induction of labor when done at the right gestational age for correct indication is beneficial to women as it reduces the complications caused due to the continuation of high-risk pregnancies.